2016
DOI: 10.1007/s00266-016-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 109 Consecutive Explanted Breast Implants: Correlation Between Suspected Implant Rupture and Surgical Findings

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The latter is unreliable because it only has a sensitivity of 30% [ 6 ]. In contrast, MRI is ideal for detecting implant rupture, with a sensitivity of 100% and specificity of 54% for detecting rupture or leakage [ 18 ]. The ‘linguine sign’ has been reported to have a sensitivity of 93% and specificity of 65% in breakage detection.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is unreliable because it only has a sensitivity of 30% [ 6 ]. In contrast, MRI is ideal for detecting implant rupture, with a sensitivity of 100% and specificity of 54% for detecting rupture or leakage [ 18 ]. The ‘linguine sign’ has been reported to have a sensitivity of 93% and specificity of 65% in breakage detection.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, there has been overall improvement in the quality and integrity of these devices; however, damage from medical instruments continues to be the cause of device failures in over 50% of reported cases. 15 Due to the nature of autologous fat transfer with multiple passes and essentially a blind technique, one can see how this may represent a high-risk procedure for treating implant damage. Interestingly, one study even suggested that left-sided implants seem to be damaged more often owing to surgeons’ overall right handedness.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of implant rupture increases with implant age. 2 Rupture rates vary according to the literature; however, studies show a single time point rupture rate of 9% to 12.2%. 3,4 The sticky, oily nature of silicone makes ruptured implant removal messy, cumbersome, time-consuming, and unpleasant.…”
mentioning
confidence: 99%